2015
DOI: 10.1621/nrs.13002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chemical Modulators of the Constitutive Activated Receptor (CAR) in a Gene Expression Compendium

Abstract: The nuclear receptor family member constitutive activated receptor (CAR) is activated by structurally diverse drugs and environmentally-relevant chemicals leading to transcriptional regulation of genes involved in xenobiotic metabolism and transport. Chronic activation of CAR increases liver cancer incidence in rodents, whereas suppression of CAR can lead to steatosis and insulin insensitivity. Here, analytical methods were developed to screen for chemical treatments in a gene expression compendium that lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 59 publications
6
102
0
Order By: Relevance
“…However, the high level of accuracy demonstrated the robustness of the computational procedures despite the fact that the biosets were derived from heterogeneous experiments with various exposure conditions carried out in multiple labs. These results are consistent with our past experience in accurately identifying chemical modulators of transcription factors in the mouse liver (Oshida et al, , , ) and MCF‐7 cells (Ryan et al, ). Our approach has a number of advantages compared to other methods used to identify DDI chemicals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the high level of accuracy demonstrated the robustness of the computational procedures despite the fact that the biosets were derived from heterogeneous experiments with various exposure conditions carried out in multiple labs. These results are consistent with our past experience in accurately identifying chemical modulators of transcription factors in the mouse liver (Oshida et al, , , ) and MCF‐7 cells (Ryan et al, ). Our approach has a number of advantages compared to other methods used to identify DDI chemicals.…”
Section: Discussionsupporting
confidence: 91%
“…The strategy for comparison of a biomarker to collections of biosets has been described in previous studies (Oshida et al, 2015a(Oshida et al, , 2015b(Oshida et al, , 2015c. Using the Running Fisher algorithm, the biomarker was compared to each bioset in BSCE.…”
Section: Comparison Of the Tgx-ddi Biomarker To Biosets In Bscementioning
confidence: 99%
See 1 more Smart Citation
“…The CAR-mediated suppression of HNF4α may lead to a decrease in glucose and lipid metabolism pathways. There are apparent interactions between CAR and other receptors such as AhR, PXR, and PPARα, because the activators for these other receptors can also activate CAR-signaling (Oshida et al, 2015). The present study has shown that activation of CAR by TCPOBOP up-regulates the AhR-target genes Cyp1a as well as many PXR-target genes, however, it actually down-regulates the PPARα-target genes in the Cyp4a family.…”
Section: Discussionmentioning
confidence: 99%
“…As its name suggests, in either the absence, but particularly in the presence of an agonist, Car heterodimerizes with the retinoid X receptor alpha and binds to cognate response elements of target genes, thereby up-regulating their transcription [reviewed in 7]. Chemical activators of Car are structurally diverse and include drugs like phenobarbital, the fungicide propiconazole, as well as synthetic compounds such as 1,4-bis(2-(3,5-dichloropyridyloxy)) benzene (TCPOBOP) [8]. …”
Section: Introductionmentioning
confidence: 99%